KONSEP PEMIKIRAN IBNU SINA TENTANG PENDIDIKAN AKHLAK - DESWITA DESWITA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
In this article, the researcher tried to discuss the thinking way of Ibnu Sina about Islamic education, especially in teaching behaviour. It was due to teaching behaviour was the basic principle to achieve the target of teaching. For Ibnu Sina, the teaching behaviour could be explored through discussion and socialization among the children of the same age. It was because they had a sense of imitation. In teaching bahaviour, a teacher had to consider the children’s psychology because this might influence the successful of teaching. Meanwhile, as a medium of teaching behaviour, Ibnu Sina had used a poem as a tool to spread the value of good behaviour.Kata kunci: pemikiran, pendidikan, akhlak